Pelatihan Penyusunan Kisi-Kisi Dan Soal Berorientasi Hots Bagi Para Guru Di Sd Negeri 091488 BAH Sampuran - Anita Debora Simangunsong; Sahat Renol HS; Nancy Angelia Purba; Marthin Fransisco Manihuruk; Golda Novatrasio Sauduran; Sahat Taruli Siahaan (SAMBARA: Jurnal Pengabdian Kepada Masyarakat, 2023)
At this time learning innovations are needed to improve students' thinking skills, one of which is by getting students used to solving HOTS-based questions. The purpose of the service activity is to train teachers of SD Negeri 091488 Bah Sampuran in preparing HOTS-based questions. The activity was carried out in two stages, the preparation stage and the implementation stage. In the preparatory stage, the service team coordinated with the Principal of SD Negeri 091488 Bah Sampuran to identify problems, determine problem solutions, determine target groups, and determine the time and place for carrying out activities. The result of this dedication was that the participants' response to the implementation of this activity was very good, this can be seen from the enthusiasm of the participants in asking questions to the speakers related to the training material provided. The conclusion of this dedication is that participants hope that this kind of activity can be rescheduled for future times.